Determination of viability in foodborne bacteria with inter-calating dyes: ethidium monoazide (EMA) and propidium monoazide (PMA) - Telli, Arife Ezgi; Doğruer, Yusuf (International Journal of Biological Research, 2017)
The ability to distinguish between living and dead cells is considered to be very important for biological researches. It is an important problem that the technology used up to day does not allow the quantitative differentiation of specific cells in a mixed cell community. Determination of whether the microorganisms present in the foods are in a viable form is an important phenomenon in determining the disease-forming potential.It is a fact that DNA, which is found in cells that lose their viability, can maintain its activity for a long time. Discrimination of live-dead cell occurs when the intercalating dye is covalently bound to DNA that is cleaved in the dead cell where membrane integrity is impaired. The formation of the covalent bond is activated by photoactivation. Inter-collating dyes only affect dead cells that are damaged by cell wall or membrane integrity. Due to the covalent binding of the inter-collating dye, DNA amplification cannot occur in PCR and other molecular techniques based on PCR.Among the non-permeable stains, it is accepted that PI is the most commonly used. PMA is identical to PI and additionally contains azide groups. Azide groups allow PMA to cross-covalently bond with DNA in bright light. Another inter-collating dyes with an azide group is ethidium mono azide (EMA).The The PMA molecule provides a higher selectivity on discrimination of live-dead cells by virtue of its’ higher charge when compared to EMA. Many researchers have combined EMA and PMA with PCR, Real-time PCR and LAMP in order to differentiate the live population of bacterial, viral, fungal and parasitic food-borne pathogens because they are claimed to be more successful in complex samples than in fluorescence based techniques.